Evaluating Syria's financial sustainabilityand its impact on banking financial sustainability (Damascus University Journal for the economic and Political sciences, 2026)
The study aimed to evaluate the financial sustainability of Syria and its impact on banking financial sustainability. The quantitative methodology was adopted in light of the study variables represented by the debt-to-GDP index, as an independent variable, and banking profitability represented by the return on assets and return on equity, as dependent variables. Simple linear regression was applied to test the effect of the independent variable on the dependent variables using IBM SPSS v.25.The study reached a set of results, the most important of which was that the debt-to-GDP ratio was increasing during the study period from 2012 to 2020, as it exceeded the acceptable threshold of 40%, which negativelyaffects the financial sustainability indicators of traditional banks, represented by the return on Assets and return on equity. The researcher recommended the necessity of making adjustments on expenditures and revenues, developing monetary policy in Syria, maintaining the sustainability rate to a minimum over successive years, and the necessity of directing government spending to productive investment.
Keywords: Syria's Financial; Sustainability; Banks' Financial Sustainability; Debt Rate; GDP